Pengaruh Ekuitas Merek dan Minat Beli Terhadap Keputusan Pembelian Kaos Polo T- Shirt Pada PT. Kaos’Ta Sukses Mulia Kota Parepare - Megawati Beddu; Nurbakti, Rezky; Muin, Saripah Aryanti Rasyid (Fakultas Bisnis Institut Ilmu Sosial dan Bisnis Andi Sapada, 2022)
This study aims to determine and explain: the effect of brand equity and buying interest on purchasing decisions on Shirt Polo T-Shirts at PT. Kaos'Ta Sukses Mulia City of Parepare, the data collection techniques used were observation, interviews, questionnaires, documentation and literature study (Library search). The population and sample in this study amounted to 30 respondents who were taken by accident. The data analysis used in this study is descriptive analysis and multiple regression. The results show that the brand equity variable partially has a significant effect on purchasing decisions, the value of tcount > ttable of 3.077 > 2.052 and a significance value of 0.005 (< 0.05 while for The buying interest variable has a positive effect on purchasing decisions for polo T-shirts at PT Kaosta Sukses Mulia Parepare City with tcount < ttable of 0.007 < 2.052 and a significance value of 0.995 (> 0.05). is 0.1%. The test results in this study state that the buying interest variable does not have a positive fcount (5,119)> ftable. (3,354 )